2010
DOI: 10.1366/000370210792434413
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fungal-Degraded Lime Wood by X-Ray Diffraction and Cross-Polarization Magic-Angle-Spinning 13C-Nuclear Magnetic Resonance Spectroscopy

Abstract: X-ray diffraction, scanning electron microscopy (SEM), and solid-state cross-polarization magic-angle-spinning (CP/MAS) (13)C-NMR spectroscopy were applied to determine changes over time in the morphology and crystallinity of lime wood (Tilia cordata Miller) generated by the soft-rot fungi. Wood samples were inoculated with Trichoderma viride Pers for various durations up to 84 days. Structural and morphological modifications were assessed by comparing the structural features of decayed lime wood samples with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Other methods to visualise and accentuate the spectral information are deconvolution of overlapping bands, a method most frequently applied to 13 C CPMAS NMR spectra (Popescu et al 2010a), calculation of difference spectra and second derivatives, or two-dimensional correlation spectra, which was in the context of fungal wood degradation applied for NMR spectra (Yelle et al 2008; Yelle et al 2011) and for IR spectra (Popescu et al 2010b). …”
Section: Ways To Extract Complex Information From Complex Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods to visualise and accentuate the spectral information are deconvolution of overlapping bands, a method most frequently applied to 13 C CPMAS NMR spectra (Popescu et al 2010a), calculation of difference spectra and second derivatives, or two-dimensional correlation spectra, which was in the context of fungal wood degradation applied for NMR spectra (Yelle et al 2008; Yelle et al 2011) and for IR spectra (Popescu et al 2010b). …”
Section: Ways To Extract Complex Information From Complex Spectramentioning
confidence: 99%
“…Popescu et al (2010a) reported the apparent increase of crystallite size in lime ( Tilia cordata ) wood degraded by Trichoderma viride —a wood-inhabiting deuteromycete—and assigned this effect to higher mobility of less ordered polysaccharide chains after selective degradation of amorphous polysaccharides. The authors investigated the same degraded wood with 2D-correlation FT-MIR spectroscopy and found decreased carbohydrate content and decreased crystallinity.…”
Section: Observations Of Alterations Due To Fungal Wood Degradation Pmentioning
confidence: 99%
“…However, CrI values were not in accordance with the respective crystallite sizes (L), as for the uncharred material, L presented the lowest value. The considerably high CrI of uncharred material was not anticipated, as in archaeological wood the crystallinity usually decreases with decay [23,[47][48][49]. Nonetheless, crystallinity's increase has been reported by other authors in initial stages of degradation due to the dramatic loss of amorphous cellulose regions [23,48,50].…”
Section: Xrdmentioning
confidence: 99%
“…3. The signals that correspond to cellulose were observed at 63 ppm (C6), 75 ppm (C2, C3, and C5), 83, 87 ppm (C4), and 104 ppm (C1) (Popescu et al 2010). It has been reported that xylans have signals at 102 ppm (C1), 84 ppm (C4), 72 to 75 ppm (C2 and C3), and 65 ppm (C5) (Wallace et al 1995); however, these signals were overlapped with the strong signals of cellulose.…”
Section: C-nmr Spectra Analysismentioning
confidence: 99%